Literature Review Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Konsumen - Ellya Dewi; Dety Mulyanti (International Forum of Researchers and Lecturers, 2023)
In the marketing concept, one way to achieve company goals is to know what are the needs and desires of consumers or target markets and how to provide the satisfaction expected by consumers / buyers effectively and efficiently. So that companies that apply marketing concepts need to pay attention to consumer behavior and factors that influence buyer decisions. This literature review aims to find out what factors influence the decision making made by consumers in buying a product. Based on the formulation of the article, results and discussions reviewed and discussed in this article, it can be concluded that there are many factors that influence consumer decisions to buy including product prices, product quality both from the product itself and its services, product promotion, location, social status and family.